2016
DOI: 10.3928/01913913-20160122-05
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Features and Long-term Surgical Outcomes in Infantile Constant and Intermittent Exotropia

Abstract: Constant deviation was associated with the development of recurrence, DVD/IOOA, and poor stereopsis after surgery. Constancy of exotropia is a reliable factor for predicting poor surgical outcomes in infantile exotropia at long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
2
11
0
1
Order By: Relevance
“…Na et al evaluated long-term outcomes in intermittent and constant exotropia after surgical correction and observed that cumulative probability of satisfactory surgical alignment three years after surgery was 92% in intermittent exotropia and 70% in constant exotropia and there was significantly more distance suppression (p=0.029) and poor stereopsis (p=0.002) in constant exotropes even after surgical treatment. 15 We also observed in our study that exotropes had a much higher chance of achieving stereopsis than esotropes. 12 (66.6%) of the 18 exotropes and 5 (41.6%) of the 12 esotropes developed stereopsis and 11 (78.5%) of the 14 satisfactorily aligned exotropes and only 5 (55.5%) of the satisfactorily aligned esotropes developed stereopsis.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Na et al evaluated long-term outcomes in intermittent and constant exotropia after surgical correction and observed that cumulative probability of satisfactory surgical alignment three years after surgery was 92% in intermittent exotropia and 70% in constant exotropia and there was significantly more distance suppression (p=0.029) and poor stereopsis (p=0.002) in constant exotropes even after surgical treatment. 15 We also observed in our study that exotropes had a much higher chance of achieving stereopsis than esotropes. 12 (66.6%) of the 18 exotropes and 5 (41.6%) of the 12 esotropes developed stereopsis and 11 (78.5%) of the 14 satisfactorily aligned exotropes and only 5 (55.5%) of the satisfactorily aligned esotropes developed stereopsis.…”
Section: Discussionsupporting
confidence: 75%
“…[13][14][15][16][17][18] It has been seen that stereopsis is easier to achieve if the strabismus is intermittent rather than constant. [13][14][15] Most intermittent exotropes attain good binocularity and stereopsis after treatment and many have good binocularity and stereopsis even before treatment due to the lack of amblyopia and the presence of time intervals in which they are orthotropic. The constant exotropes, whereas, have poorer preoperative binocularity and though they have substantial improvement in binocularity postoperatively, it is less than that of the intermittent exotropes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Erken gelişim döneminde, görme eksenlerinin paralelliğini kaybetmesi (göz kayması), düzeltilmemiş kırma kusurları veya beyne gözden net görüntü gitmesini engelleyen katarakt, kapak düşüklüğü (ptozis) gibi göz patolojileri sonucu ortaya çıkan bozulmuş görsel uyaranlar sonucu gelişir. (Na & Kim, 2016) Ambliyopi açısından bakıldığında ekzotropyalarda daha az ambliyopi görülür. Bunun nedeni olarak alternansın daha sık olması ve her iki gözün benzer oranda kullanılması olduğu düşünülmektedir.…”
Section: Resim -9unclassified